Conductive nerve conduit with piezoelectric properties for enhanced PC12 differentiation - Hamideh Javidi; Ahmad Ramazani Saadatabadi; S. K. Sadrnezhaad; Najmeh Najmoddin (Scientific Reports, 2023)
Abstract Restoration of nerve tissue remains highly challenging, mainly due to the limited regeneration capacity of the nervous system and the development of fibrosis. This limitation necessitates designing new nerve guidance channel to promote nerve repairing. In this study, we developed a novel core/shell conduit to induce PC12 differentiation. Co-electrospinning method was utilized to produce a fibrous shell containing polycaprolactone/polyvinylidene fluoride PCL/PVDF, gelatin and polyaniline/graphene (PAG) nanocomposite. The core section of the conduit was filled with chitosan–gelatin hydrogel containing PAG and ZnO nanoparticles. Such conduit shows antibacterial activity, electrical conductivity and piezoelectric property. The effect of such engineered conduit on PC12 differentiation was investigated by analyzing differentiation markers Nestin and microtubule-associated protein 2 (MAP2) through immunocytochemistry and PCR-RT techniques. The result revealed that such conduit could significantly induce Nestin and MAP2 gene expression in the PC12 cells and, thus, it is a viable option for effective cell differentiation and nerve regeneration.